Laba-Laba Famili Araneidae pada Kawasan Cagar Alam Lembah Anai Kabupaten Tanah Datar, Sumatera Barat - Fithria Diniyati; Dahelmi Dahelmi; Henny Herwina (Jurnal Biologi Universitas Andalas, 2018)
An inventory of spiders araneidae (Arachnida: Araneae) from Nature Reserve Lembah Anai, Tanah Datar , West Sumatra was conducted from March to December 2015 by using the sweeping, hand collection,  beating and sieving methods. From a total of  37  individuals , we identified  to 9 species that belong to 6 genera.  Araneus has the top species number of species (3 species), while, Acusilas, Clycosa, Argiope, Gasteracantha, Larinia and Nephila were found only one species for each one.